Terminal decline in well-being: The role of multi-indicator constellations of physical health and psychosocial correlates - Andreas M. Brandmaier; Nilam Ram; Gert G. Wagner; Denis Gerstorf (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Well-being is often relatively stable across adulthood and old age, but typically exhibits pronounced deteriorations and vast individual differences in the terminal phase of life. However, the factors contributing to these differences are not well understood. Using up to 25-year annual longitudinal data obtained from 4,404 now-deceased participants of the nationwide German Socio-Economic Panel Study (SOEP; age at death: M = 73.2 years; SD = 14.3 years; 52% women), we explored the role of multi-indicator constellations of socio-demographic variables, physical health and burden factors, and psychosocial characteristics. Expanding earlier reports, Structural Equation Model Trees (SEM Trees) allowed us to identify profiles of variables that were associated with differences in the shape of late-life well-being trajectories. Physical health factors were found to play a major role for well-being decline, but in interaction with psychosocial characteristics such as social participation. To illustrate, for people with low social participation, disability emerged as the strongest correlate of differences in late-life well-being trajectories. However, for people with high social participation, whether or not an individual had spent considerable time in the hospital differentiated high vs. low and stable vs. declining late-life well-being. We corroborated these results with Variable Importance measures derived from a set of resampled SEM Trees (so-called SEM forests) that provide robust and comparative indicators of the total interactive effects of variables for differential late-life well-being. We discuss benefits and limitations of our approach and consider our findings in the context of other reports about protective factors against terminal decline in well-being.
Keywords: 330; successful aging; life satisfaction; SEM forest; SEM tree; German Socio-Economic Panel Study